PROMOTING OF TEACHERS’ COMMUNICATIVE COMPETENCE IN MEDIATION STUDIES WITHIN THE LIFE QUALITY CONTEXT - Nicmane, Lolita Terēze; Baltušīte, Regīna; Katane, Irēna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Living in a society, people cannot avoid communicating with others. Communication accompanies us in all spheres of life. Consequently, it is important to develop our communicative competence over a lifetime. Teacher is one of the professions where communicative competence determines the efficiency of activity. Communicative competence can be developed in various ways. Mediation was introduced in the justice system at the end of the 20th century as a method of dispute solving with the participation of a mediator. In recent years, mediation knowledge and skills are also gradually taking a rightful place in the field of education. Experience acquired during the mediation studies is valuable for the promotion of the communicative competence: knowledge and skills on conflict solving, dialogue maintenance, active listening etc., which helps in creating of positive psychological environment in any organisation (including schools). Consequently, teachers must be able to solve conflict situations, and, which is equally important, to pass on their experience to their colleagues, students and their parents. The aim of the research: based on the results of theoretical researches, to make a survey aimed at finding out the opinion of teachers concerning the importance of the communicative competence in the life quality improvement. 97 % of respondents believe that there is a link between the communicative competence and the quality of life.